'I think writing is everything': An exploration of the writing experiences of people with aphasia. Issue 6 (5th August 2022) - Thiel, Lindsey; Conroy, Paul
Abstract: Background: Written communication has become an increasingly important part of everyday life in social, educational and professional spheres. The substantial increase in writing via the internet and mobile technologies provides both an opportunity for social engagement and distinct challenges for people with aphasia. Within the current literature there has been limited research into the lived experiences of people with aphasia of their writing difficulties and how these affect their ability to communicate. Aims: This qualitative study aimed to explore the experiences of people with aphasia of living with language‐related writing difficulties and the impact of these on their lives. Methods & Procedures: Eight people with post‐stroke aphasia and writing difficulties took part in semi‐structured interviews. The interviews were analysed using inductive reflexive thematic analysis. Outcomes & Results: Two themes were found in the data. The first theme was a gradual and effortful improvement to writing : Participants described how writing had improved since their stroke due to strategies and support, but they still found writing to be difficult and frustrating and described many barriers to writing. The second theme was the importance of writing for fulfilling adult social roles : Participants found writing to be important for communicating with family, friends and organizations, but their participation in society and self‐esteem and confidence were impacted by writing difficulties; reduced social roles meant reduced need for writing, but participants were still motivated to work towards writing goals. Conclusions & Implications: The findings demonstrate the emerging importance of writing skills for people with aphasia with respect to communication, well‐being, participation and inclusion in society, and carrying out social roles. They provide an insight into the process of improvement, including the difficulties, facilitators and barriers. Implications for speech and language therapy assessment and management are discussed. WHAT THIS PAPER ADDS: What is already known on the subject: People with aphasia have difficulties with writing that can affect their ability to communicate. A small body of qualitative research has provided insights into individuals' experiences of literacy difficulties. More research is needed to understand the writing experiences of people with aphasia to help design appropriate assessments and interventions. What this paper adds to existing knowledge: Participants experienced gradual and effortful improvement since their stroke. They felt negative about aspects of their writing, including speed, accuracy and range of vocabulary. Writing was facilitated through assistive technologies, spelling practice and support from others; barriers included technology, lack of time, stroke‐related symptoms and others' lack of awareness about aphasia. Participants considered writing skills to be important, particularly for communication, carrying out adult social roles and participating in society, and were therefore still working towards goals related to everyday writing activities. What are the potential or actual clinical implications of this work?: This study suggests that speech and language therapy assessment should include interviewing participants about their activities, strengths, difficulties, facilitators and barriers in writing, and informal assessment of a range of functional writing tasks. Intervention should be tailored to the individual's needs. This should include meaningful activities that relate to functional everyday writing and, where appropriate, self‐management, compensatory technologies and group approaches, while making use of existing strategies identified by the individual.